Changes in urinary concentrations of contemporary and emerging chemicals in commerce during the COVID-19 pandemic: Insights from the Environmental influences on Child Health Outcomes (ECHO) program - Megan E. Romano; Jessie P. Buckley; Xiuhong Li; Julie B. Herbstman; Kurunthachalam Kannan; Sunmi Lee; Susan L. Schantz; Leo Trasande; Margaret R. Karagas; Frederica Perera (PLoS ONE, 2025)
Previous research indicates that the COVID-19 pandemic catalyzed alterations in behaviors that may impact exposures to environmental endocrine-disrupting chemicals. This includes changes in the use of chemicals found in consumer products, food packaging, and exposure to air pollutants. Within the Environmental influences on Child Health Outcomes (ECHO) program, a national consortium initiated to understand the effects of environmental exposures on child health and development, our objective was to assess whether urinary concentrations of a wide range of potential endocrine-disrupting chemicals varied before and during the pandemic. Drawing from three racially, ethnically, and socioeconomically diverse ECHO cohorts, we assessed key differences in urinary chemical concentrations related to environmental exposures through food packaging, use of disinfectants, personal care products and air pollutants using repeated urine samples in a subset of 47 participants, who contributed a urine sample prior to the pandemic (between October 2018 and February 2020) and a subsequent urine sample after the pandemic began (between March 2020 and April 2021). We measured urinary concentrations of analytes across several chemical groups, including polycyclic aromatic hydrocarbons (PAHs), phthalates/alternative plasticizers, synthetic phenols (parabens, bisphenols, triclosan, benzophenones), organophosphate esters (OPEs), insecticides and fungicides. Multivariable linear mixed models accounting for key covariates and clustering within cohort and across repeated samples were used to estimate the change in urinary analyte concentrations across time points. We observed decreases in urinary concentrations of some PAHs, bisphenols, benzophenones, and triclosan, and increases in specific OPEs. These biomarker data mirror some of the behavior changes reported in our prior work and support the observation that the pandemic-related behavior changes lead to alterations in chemical exposures that have been linked to adverse health outcomes.